2015
DOI: 10.5527/wjn.v4.i3.374
|View full text |Cite
|
Sign up to set email alerts
|

Early renal failure as a cardiovascular disease: Focus on lipoprotein(a) and prothrombotic state

Abstract: Patients with renal failure are at increased risk of cardiovascular events even at the earliest stages of disease. In addition to many classic cardiovascular risk factors, many conditions that are commonly identified as emerging risk factors might contribute to occurrence of cardiovascular disease. Changes in circulating levels of many of these emerging risk factors have been demonstrated in patients with early stages of renal failure caused by different types of renal disease and have been associated with det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Support to a possible role of Lp(a) in the development and progression of renal dysfunction has been provided also in other studies [203,204], although in the Chronic Renal Insufficiency Cohort (CRIC) study that enrolled 3939 adults with chronic kidney disease, mostly diabetics, none of the circulating lipids, including Lp(a), were significantly associated with progression of kidney disease [205]. Further work is needed to better understand the complex relationship between Lp(a) and renal disease, although it should be kept in mind that increased Lp(a) levels are one the main contributors to the increased cardiovascular risk found in patients with progressive renal disease [206].…”
Section: Lp(a) and Hypertensive Renal Damagementioning
confidence: 99%
“…Support to a possible role of Lp(a) in the development and progression of renal dysfunction has been provided also in other studies [203,204], although in the Chronic Renal Insufficiency Cohort (CRIC) study that enrolled 3939 adults with chronic kidney disease, mostly diabetics, none of the circulating lipids, including Lp(a), were significantly associated with progression of kidney disease [205]. Further work is needed to better understand the complex relationship between Lp(a) and renal disease, although it should be kept in mind that increased Lp(a) levels are one the main contributors to the increased cardiovascular risk found in patients with progressive renal disease [206].…”
Section: Lp(a) and Hypertensive Renal Damagementioning
confidence: 99%
“…The association between kidney function and lipoprotein(a) levels has received interest since the initial observation of elevated lipoprotein(a) levels among dialysis patients in the end of 20th century (26). Previous studies showed the association of eGFR and lipoprotein(a) that higher lipoprotein(a) levels have been observed with reduced eGFR, even in the earliest stages of renal impairment (24,(27)(28)(29)(30)(31). Our results also show that there is an inverse correlation between lipoprotein(a) and eGFR in patients undergoing CAG.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potential effects of lipoproteins and statins, our study has adjusted for those potential confounders. The possible underlying mechanism may be lipoprotein(a) potentially constitutes a molecular link between the processes of atherosclerosis (mediated by the LDL-like moiety) and thrombosis [mediated by the apo(a) moiety] that together precipitate events such as myocardial infarction and ischemic stroke ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism is the decreased renal scavenging capability of Lp(a) in patients with renal failure, which has been demonstrated by the distribution difference of the plasma Lp(a) concentration in renal arteries and veins and by the urine apolipoprotein A fragments (22). Such a negative correlation between Lp(a) levels and renal function, triggering a vicious circle, leads to CVEs even in patients with early renal impairment (22,24).…”
Section: Discussionmentioning
confidence: 99%